On-demand service platform operations management: A~literature review and research agendas - Xiaoyu Yan; Weihua Liu; Victor Shi; Tingting Liu (Modern Supply Chain Research and Applications, 2022)
Purpose - The literature review aims to facilitate a broader understanding of on-demand service platform operations management and proposes potential research directions for scholars. Design/methodology/approach - This study searches four databases for relevant literature on on-demand service platform operations management and selects 72 papers for this review. According to the research context, the literature can be divided into research on "a single platform" and research on "multiple platforms". According to the research methods, the literature can be classified into "Mathematical Models", "Empirical Studies", "Multiple Methods" and "Literature Review". Through comparative analysis, we identify research gaps and propose five future research agendas. Findings - This paper proposes five research agendas for future research on on-demand service platform operations management. First, research can be done to combine classic research problems in the field of operations management with platform characteristics. Second, both the dynamic and steady-state issues of on-demand service platforms can be further explored. Third, research employing mathematical models and empirical analysis simultaneously can be more fruitful. Fourth, more research efforts on the various interactions among two or more platforms can be pursued. Last but not least, it is worthwhile to examine new models and paths that have emerged during the latest development of the platform economy. Originality/value - Through categorizing the literature into two research contexts as well as classifying it according to four research methods, this article clearly shows the research progresses made so far in on-demand service platform operations management and provides future research directions.
Keywords: 650; Literature review; On-demand platform; Platform operations management; Service platform